Temperate coastal wetland near-surface carbon storage: Spatial patterns and variability. (5th April 2020) - Owers, Christopher J.; Rogers, Kerrylee; Mazumder, Debashish; Woodroffe, Colin D.
Abstract: Carbon mitigation services provided by coastal wetlands are not spatially homogeneous, nevertheless are commonly described on the basis of vegetation distribution within the intertidal zone. Distribution of mangrove and saltmarsh varies in response to frequency of tidal inundation, resulting in environmental gradients in edaphic factors that influence vegetation structure, and subsequently affect sedimentary carbon additions by vegetation and carbon losses by decomposition. Current sampling approaches and reporting do not adequately account for variability of carbon storage within a wetland, and assessments need to capture spatial variation associated with carbon storage to improve estimates of potential carbon mitigation services by natural ecosystems. This study quantifies the variation in near-surface carbon storage (i.e. upper 30 cm) across an intertidal gradient using a stratified sampling approach that recognises vegetation structure. Vegetation distribution and structure, as well as sedimentary controls on carbon content, explained variation in carbon storage. Saltmarsh near-surface carbon storage varied considerably between structural form. This was less evident for mangrove structural forms (i.e. tall, shrub, dwarf), which may be due to mangrove roots extending to depths beyond 30 cm. Sedimentary characteristics correlated with carbon content, demonstrating considerable influence on near-surface carbon storage within a wetland. The principal finding of this study was that variation within a wetland corresponds to the variation between sites. Stable carbon isotopes offer a means to identify previous vegetation contributions to sediment, associated with an earlier stage of wetland development, likely reflecting previous environmental conditions. A stratified sampling approach that recognises vegetation structure provides the capacity to account for variability of carbon within a wetland that is inadequately described by current sampling protocols. Graphical abstract: Image 1 Highlights: Carbon storage variation with a wetland corresponds to variation between sites. Assessments of carbon storage should recognise vegetation structure. Previous environmental conditions may be identified using stable carbon isotopes.